Pendampingan Sosialisasi Penerimaan Mahasiswa Baru Universitas Nurul Jadid melalui Media Sosial dan Video Profil di Sekolah Mitra - Syafiih, M; Kholilur Rahman, Moh. Nur; Khowwas, Aliyul; Ghufron, Khairul; Maulana, Iqbal (Jurnal Ilmiah Pengabdian dan Inovasi, 2025)
This community service project was initiated to support the student admission process of Universitas Nurul Jadid by enhancing its promotional strategies through social media and school partnerships. The growing importance of digital platforms in education marketing, especially among high school students, makes this topic highly relevant. The program focused on assisting the university's outreach efforts by conducting socialization activities in partner schools and developing engaging promotional content, such as university profile videos and targeted social media campaigns. The method used was participatory assistance, involving collaboration between university staff, students, and school representatives to ensure effective dissemination of information. Activities included workshops, media content creation, and direct engagement sessions in partner schools. The results showed a significant increase in awareness and interest among students regarding the university’s programs and facilities. Furthermore, social media analytics indicated improved engagement with the posted content. This initiative not only strengthened the relationship between Universitas Nurul Jadid and its partner schools but also contributed to a more modern and effective student recruitment strategy. In conclusion, leveraging digital media in collaboration with educational partners proved to be a valuable approach in promoting higher education opportunities to prospective students.